1996
DOI: 10.1148/radiology.198.1.8539401
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic tumors: predisposing factors for complications of transcatheter oily chemoembolization.

Abstract: Most patients with major complications after TOCE had preexisting risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
1
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(208 citation statements)
references
References 0 publications
7
194
1
6
Order By: Relevance
“…We did not observe any relation between baseline characteristics and the occurrence of adverse events. Risk factors for TACErelated adverse events have been described in studies focusing on hepatocellular carcinoma (Chung et al, 1996) (portal vein obstruction, biliary anastomosis or obstruction, compromised functional hepatic reserve). Except two patients who had a previous story of duodenopancreatectomy, none of our patients had such risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any relation between baseline characteristics and the occurrence of adverse events. Risk factors for TACErelated adverse events have been described in studies focusing on hepatocellular carcinoma (Chung et al, 1996) (portal vein obstruction, biliary anastomosis or obstruction, compromised functional hepatic reserve). Except two patients who had a previous story of duodenopancreatectomy, none of our patients had such risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of major complications has been reported to be less than 5%, including hepatic insufficiency, liver abscess, parenchymal infarction, intrahepatic aneurysm, pulmonary embolism, ischemic cholecystitis or gallbladder infarction, bone marrow depression, liver rupture, and gastric or duodenal ulceration [340]. Important predisposing factors are major portal vein obstruction, compromised hepatic functional reserve, biliary obstruction, previous biliary surgery, excessive amount of iodized oil, and nonselective embolization [341]. TACE does not induce significant liver dysfunction in patients with C-P class A or B cirrhosis despite embolization of relative proximal hepatic arteries [342].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…Chung's (Chung et al, 2007) research indicated that there was still certain concentration drugs in liver parenchyma surrounding the iodized oil deposition areas. It is thus evident that several drugs released into no cancer tissues were inevitable, which could cause hepatic injury or liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hong Li 1 *, Yaohong Hu 2 , Na Li 2 , Yan Zhou 1 in liver parenchyma (Chung et al, 1996;Bruix 1997) and cell necrosis was visible (Therasse et al, 2000;Kamada et al, 2001) surrounding the iodized oil deposition areas. So only using super-selective intubation treatment to reduce the liver fibrosis that caused by TACE was not enough, because hepatocarcinoma were not that sensitive to chemotherapeutics, and liver fibrosis was caused by huge doses chemotherapeutics drugs in TACE.…”
Section: Liver Fibrosis and Five Year Survival Of Hepatocellular Cancmentioning
confidence: 99%